A case of basaloid follicular hamartoma - REN Xinxin; ZHANG Xinyan; JI Shuangshuang; GUO Ling (Pifu-xingbing zhenliaoxue zazhi)
We report a case of basaloid follicular hamartoma. A 53-year-old female patient presented with a one-year history of widespread papules on the scalp, occasionally accompanied by itching. Dermatological examination revealed numerous light brown papules, sized approximately 1~3 mm in diameter, diffusely distributed across the scalp, with the highest density in the occipital region. Some papules had coalesced. No hypertrichosis or depressions on the palms and soles were observed. Histopathology of the skin lesion revealed irregular proliferation of basaloid cells, forming multiple cell nests composed of basaloid cells embedded within a fibrous matrix. The nests were irregular in shape, with no significant cellular atypia or evident mitotic figures. Peripheral cells were arranged in a palisading pattern, with no retraction spaces between the nests and surrounding connective tissue. Amyloid deposits were observed within the matrix. Immunohistochemistry revealed CD34 positivity in the fibrous stromal cells surrounding the tumor; Bcl-2 expression was limited to a few basal cells at the outermost layer of the lesion. Diagnosis: basaloid follicular hamartoma. The patient did not respond well to electrolysis and cryotherapy with liquid nitrogen, and the rash continued to progress. The patient is still under follow-up.